2016
DOI: 10.1515/zsr-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Wenig gebildet, viel sanktioniert? Zur Selektivität von Sanktionen in der Grundsicherung des SGB II

Abstract: Welfare benefit recipients who are subject to benefit sanctions live below the subsistence level for a fixed period of time. Individuals with low education bear an increased risk of being sanctioned. Quantitative analyses of linked administrative and survey data indicate that this increased risk cannot be attributed to a lower motivation to work or a lower willingness to make concessions regarding job offers. Our analyses of qualitative interviews and individual case files reveal complex processes: Low cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
1
3
0
3
Order By: Relevance
“…These coercive elements of activation policies have received broad attention in the corresponding research. In particular, sanctioning practices have been a focal point in welfare‐state research, both in the German (e.g., Grüttner, Moczall, & Wolff, ; Zahradnik et al, ) as well as in other institutional contexts (Caswell & Høybye‐Mortensen, ; Soss, Fording, & Schram, ). Studies that focus on support and counseling, on the other hand, are far less frequent and knowledge is still patchy (Caswell et al, , p. 182).…”
Section: Discussionmentioning
confidence: 99%
“…These coercive elements of activation policies have received broad attention in the corresponding research. In particular, sanctioning practices have been a focal point in welfare‐state research, both in the German (e.g., Grüttner, Moczall, & Wolff, ; Zahradnik et al, ) as well as in other institutional contexts (Caswell & Høybye‐Mortensen, ; Soss, Fording, & Schram, ). Studies that focus on support and counseling, on the other hand, are far less frequent and knowledge is still patchy (Caswell et al, , p. 182).…”
Section: Discussionmentioning
confidence: 99%
“…Young people from poor backgrounds are less likely to possess knowledge about procedures and competencies that would enable them to take advantage of active labour market programmes, comply with behavioural requirements, and to negotiate individual preferences. Studies have revealed social differences in institutional counselling procedures [65,66], which can be interpreted as one facet of unequal capabilities in the VR process.…”
Section: Discussionmentioning
confidence: 99%
“…Zudem bestehen Hinweise, dass dieses implizite Wissen zum Umgang mit dem Beratungspersonal in sozial benachteiligten Bevölkerungsschichten weniger verbreitet ist. Denn Menschen mit geringerem oder ohne Schulabschluss mangelt es an Wissen zu erfolgreichem Handeln im Jobcenter (Zahradnik et al 2016). Sie verfügen über ein geringeres kulturelles Kapital und stehen dem Beratungspersonal aufgrund der unterschiedlichen sozialen Herkunft und sozialen Position (siehe für die Arbeitsvermittlung auch Ludwig-Mayerhofer et al 2014; für die Beratung allgemein McLeod 2013, S. 485 ff.)…”
Section: Rahmenadäquates Handeln Im Aktivierungsparadigmaunclassified
“…in einer habituellen Distanz gegenüber. Diese Faktoren erhöhen auch das Sanktionsrisiko der sozial Benachteiligten (Zahradnik et al 2016). Schwierigkeiten der Arbeitsuchenden jenseits ihrer sozialen und gesellschaftlichen Basis zu betrachten, kann dazu führen, diese Schwierigkeiten in unangemessene Hilfsmuster einzupassen und Konflikte als Beziehungsprobleme zwischen Beratungspersonal und ihrem Gegenüber zu interpretieren (Thiersch 2013, S. 213).…”
Section: Rahmenadäquates Handeln Im Aktivierungsparadigmaunclassified